The Relationship between Nutrition and COVID-19 Symptoms among Nursing Faculty Students - Abdulabbas, Hussein Ali; Hussein, Mohammed Abbas; Hindy, Hayder Abdul-Amir Maki Al (South Asian Journal of Social Sciences and Humanities, 2024)
The COVID-19 pandemic, declared a global health crisis by the WHO, has prompted significant shifts in lifestyle and health behaviors worldwide. This study investigates the relationship between dietary habits and manifestations of COVID-19 among nursing students in the Faculty of Nursing at the University of Babylon, employing a descriptive cross-sectional methodology. Drawing from a sample of 100 students, data was collected using a structured questionnaire encompassing demographic information, COVID-19 symptoms, and dietary patterns. Statistical analyses were conducted using SPSS V.23 and Excel 2016. Results indicated a predominantly female (61%) sample, with most participants being unmarried (64%). Common COVID-19 symptoms reported included loss of smell and taste (for one week), cough with secretions, high temperature, and shortness of breath. The study observed discrepancies in symptom presentation compared to previous research, highlighting variations in manifestations among populations. Notably, individuals who consumed vegetables demonstrated a lower risk of COVID-19 complications, suggesting a potential protective role of vegetable intake against the virus. However, no significant correlations were found between demographic factors and COVID-19 manifestations. Based on the findings, recommendations are proposed to promote healthier dietary practices among individuals, emphasizing the consumption of fresh fruits and vegetables, eggs, and nutrient-rich foods to aid in COVID-19 recovery. Additionally, suggestions include regular meal consumption, hydration, and moderation of caffeine intake. In conclusion, this study underscores the importance of nutrition in mitigating the impact of COVID-19 and provides valuable insights into dietary behaviors among nursing students during the pandemic. Future research should explore longitudinal associations between diet and COVID-19 outcomes to inform public health interventions and preventive strategies effectively.